Sukces edukacyjny szkoły w aspekcie psychologii pozytywnej - Krzaczkowska, Beata (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
Knowledge from the field of positive psychology, concentrated around values and personal resources, serves as a basis for effective education. Positive psychology emphasizes the value of work founded in resources and personal strengths, his virtues, merits, and developmental potential conducive to self-realization, transgression, and achieving psychological wellbeing in pursuit for happiness in the hedonistic and eudemonistic dimension. In this article, the author discuss psychological aspects of educational success, which includes not only tests and result oriented approach, but above that universal progressof students, their attitudes and values. Only if we take into consideration broad spectrum of human capabilities in the process of education, as well as highlight the importance of good and meaningful live, we will be able to open the doors for personal and educational success in live of all pupils.
Keywords: autonomia, kreatywność; logodydaktyka; poczucie dobrostanu psychicznego; psychologia pozytywna; somokontrola emocjonalna; sukces edukacyjny; współpraca